Analisis Pengaruh Cita Rasa, Persepsi Harga, dan Kualitas Pelayanan terhadap Keputusan Pembelian Konsumen di Industri Kuliner - Multriarti, Retno; Silitonga, Parlagutan (Journal of Economics, Bussiness and Management Issues, 2025)
The culinary industry is one of the business sectors that continues to grow along with consumers' increasing needs and preferences for food and beverages. This study aims to analyze the influence of taste, price perception, and service quality on consumer purchasing decisions in the culinary industry. The research method used is a survey with a quantitative approach, where data is collected through questionnaires distributed to 200 respondents using accidental sampling techniques. The independent variables in this study include taste, price perception, and service quality, while the dependent variable is consumer purchasing decisions. Data analysis was carried out using the Structural Equation Modeling (SEM) method with the help of SmartPLS software. The results of the study showed that the three independent variables have a significant influence on consumer purchasing decisions. Of the three factors, taste has the most dominant influence, followed by service quality and price perception. This indicates that consumers' sensory experience of food plays a major role in determining their purchasing decisions. The findings of this study provide practical implications for business actors in the culinary industry in developing more effective marketing strategies. By improving the quality of food taste, providing better service, and offering prices that are in accordance with consumer perceptions, business actors can increase customer satisfaction and encourage increased loyalty and sales.